The impact of shocks on gender-differentiated asset dynamics: Evidence from Bangladesh - Rakib, Muntaha; Matz, Julia Anna (International Food Policy Research Institute, 2014)
This policy note summarizes research that builds on existing studies on the gender-differentiated impacts of shocks on household asset holdings in Bangladesh, which is among the countries most vulnerable to climate change because of its densely populated coastal area and large population living below the poverty line.